IMPLEMENTING CENTRAL COMPOSITE DESIGN FOR THE FABRICATION OF SELECTIVE SEROTONIN RE-UPTAKE INHIBITOR BASED IN SITU FORMING BIODEGRADABLE DRUG DELIVERY SYSTEM - S., SRUTHI; S., GOPINATH; STANLEY A., MERITON; KUMAR S., SATHEESH; M., RISHAANTH (International Journal of Applied Pharmaceutics, 2025)
Objective: The current study aims to develop and optimize an injectable fluvoxamine-loaded biodegradable implant utilizing PLGA 50:50 as the polymer and PEG 6000 as the surfactant to tailor depression therapy. Methods: A systematic preformulation study assessed the physical and chemical properties of Fluvoxamine, including solubility, melting point, and compatibility through FTIR, DSC, and PXRD. A central composite design was used to optimize the implant formulation, evaluating critical parameters such as drug release profiles at 2 and 6 h. Surface morphology was analyzed using SEM to confirm the structural integrity of the implants. Results: Studies on preformulation validated the stability and compatibility of the medication. Central Composite design showed that an increment of PEG concentration demonstrated a significant negative effect on Y1 response, while PLGA concentration had a positive impact on Y2. The optimized formulation showed experimental values of 2.60% for the initial burst after 2 h and 19.96% for the release after 6 h. SEM analysis revealed uniform implant morphology, supporting consistent drug delivery. Conclusion: An optimized Fluvoxamine-loaded biodegradable implant formulation with minimum burst release and maximum sustained release was developed as an innovative solution for MDD management, addressing the challenges of conventional therapies. This approach offers improved bioavailability, patient compliance, and therapeutic outcomes, paving the way for advanced treatment strategies in depression management.